Уламжлалт хэлшинжлэлийн сурвалжууд дахь Гунгаажалцаны 44, Чойжи-Одсэрийн 123 үсэг гэдэг ойлголтын тодруулга: An explanation on 44 alphabetic letters by Gungaajaltsanand 123 letters by Choiji-Odser in the traditional linguistic sources - Д., Заяабаатар (Mongolian Studies, 2023)
Analyzing survey the traditional linguistic sources is an important step in historical study of the Mongolian grammar. This paper gives a definite explanation of how to understand on the 44 alphabetic letters by Gungaajaltsan and 123 by Choiji-Odser. In this paper I made following offers: Gungaajaltsan hasn’t counted o, u, ö and ü in Mongolian alphabet because these letters consist the compound graphemes such as ‘áleph+waw’ and ‘áleph+waw+yod’ like ‘ng’. The reason for this is, he has emphasized the graphic representation without considering phonetic form. Choiji-Odser has counted seven vowels, seventeen consonants and one morpheme (iyar) in the Mongolian alphabet. The sixteen consonants except ‘ng’ are formed with seven vowels. Furthermore, he has added four consonants such as p, š, j which have been changed the glyphs b, s and j at the beginning of a word as well as ng. The letter ‘j’ is written the difference when appearing at the beginning and in the middle of a word. Although they are formed with the vowels which are at the beginning (J) and in the middle (j) of a word. Obviously, it has been shown Choiji-Odser made some mistakes when he described the Mongolian alphabet.